Biomimetic lipid bilayers on solid surfaces: models for biological interactions - Kilic, Abdulhalim; Kok, Fatma Nese (Emerald, 2016)
Biomimetic lipid bilayer platforms on solid supports, or solid-supported lipid bilayers (SLBs), are important model membrane systems for studying the fundamental properties of biological membranes and their constituent lipid and protein molecules. SLBs with different properties and functionalities can be designed by changing their lipid content (charged, uncharged, saturated, etc.), adding various membrane components (glycolipids, cholesterol, etc.) or incorporating membrane proteins (receptors, ion channels, etc.). They allow the usage of surface-sensitive characterization techniques such as atomic force spectroscopy, surface plasmon resonance (SPR) and the use of acoustic sensors such as quartz crystal microbalance with dissipation monitoring (QCM-D). Both QCM-D and SPR can supply information about binding events on surfaces and the properties of the resulting lipid films in real time by using frequency-dissipation changes and refractive index shift, respectively. In recent years, the potential of SLBs in numerous practical applications, such as the construction of drug screening or cancer cell detection platforms, has been explored. These platforms address some of the important challenges faced in cell membrane and membrane protein research and make membrane-related applications possible.